Concentration and time-dependent amyloidogenic characteristics of intrinsically disordered N-terminal region of Saccharomyces cerevisiae Stm1 - Subbaiah S P, Venkata; Uttamrao, Patil Pranita; Das, Uttam; Sundaresan, Sruthi; Rathinavelan, Thenmalarchelvi (Frontiers in Microbiology, 2023)
Saccharomyces cerevisiae Stm1 protein is a ribosomal association factor, which plays an important role in preserving ribosomes in a nutrition-deprived environment. It is also shown to take part in apoptosis-like cell death. Stm1 N-terminal region (Stm1_N1-113) is shown to recognize purine motif DNA triplex and G-quadruplex. Circular dichroism (CD) spectra of Stm1_N1-113 (enriched in positively-charged Lysine and Arginine; negatively-charged Aspartate; polar-uncharged Threonine, Asparagine, Proline and Serine; hydrophobic Alanine, Valine, and Glycine) collected after 0 and 24 h indicate that the protein assumes beta-sheet conformation at the higher concentrations in contrast to intrinsically disordered conformation seen for its monomeric form found in the crystal structure. Thioflavin-T kinetics experiments indicate that the lag phase is influenced by the salt concentration. Atomic force microscopy (AFM) images collected for a variety of Stm1_N1-113 concentrations (in the range of 1–400 μM) in the presence of 150 mM NaCl at 0, 24, and 48 h indicate a threshold concentration requirement to observe the time-dependent amyloid formation. This is prominent seen at the physiological salt concentration of 150 mM NaCl with the fibrillation observed for 400 μM concentration at 48 h, whereas oligomerization or proto-fibrillation is seen for the other concentrations. Such concentration-dependent fibrillation of Stm1_N1-113 explains that amyloid fibrils formed during the overexpression of Stm1_N1-113 may act as a molecular device to trigger apoptosis-like cell death.